Metastatic ameloblastoma responding to combination chemotherapy: case report and review of the literature - Hassouni Khaled; Kebdani Tayeb; M'rabti Hind; Boutayeb Saber; Iraqui Meryem; Belbaraka Rhizlane; Fadoukhair Zouhour; Amzerin Mounia; Benjaafar Najib; El Gueddari Brahim K; Errihani Hassan (Journal of Medical Case Reports, 2011)
Abstract Background Ameloblastoma is a rare benign odontogenic tumor with locally aggressive behavior and a high recurrence rate. When metastases occur, which are uncommon, lungs constitute the most frequent site involved. Malignant ameloblastomas are different from ameloblastic carcinomas. Malignant ameloblastomas are tumors considered metastatic despite the appearance of well-differentiated or benign histology, while ameloblastic carcinomas are histologically malignant in both primary and metastatic sites. Case presentation A 24-year-old Moroccan man presented a malignant ameloblastoma of the mandible. The tumor was entirely resected. Five years later, a local recurrence occurred. Our patient was treated by exclusive radiotherapy with persistence of a residual disease. After two years he developed multiple lung metastases. Our patient received a combination chemotherapy using doxorubicin and cisplatin. Conclusion Less than 50 cases of ameloblastoma with metastases have been reported. There is still no standard treatment for metastatic ameloblastoma. Only through continuous reporting of such cases will clinicians be able to draw an optimal strategy for management of this pathology.